An Investigation on the Use of Navigation Devices in Smart Transportation Systems - Bazzan, Ana L. C.; Azzi, Guilherme G. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2012)
In large urban areas, until recently, people used to choose a route having in mind the general, high-level mental map of the urban traffic network. With the dissemination of the use of navigation devices such as GPS, all roads may now be part of a path. Therefore two questions arise, that are related to the performance of the traffic network as a whole, and to the effects of the use of these navigation devices on travelers that usually only do short trips in their own neighborhoods. Our preliminary results show that the average overall travel times indeed decrease with the use of GPS. However, travelers who used to avoid arterial roads are strongly penalized.